Participatory Strategies for Empowering Indonesian Migrant Worker Unions in Kuala Lumpur, Malaysia: Improving Welfare and Rights - Setyaning, Alldila Nadhira Ayu; Nursyamsiah, Siti (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesian migrant workers in Malaysia face various challenges, including legal uncertainty, discrimination, and unsafe working conditions. The presence of a union plays a crucial role in providing protection, advocacy, and support for these workers. This study aims to empower Indonesian migrant worker unions in Malaysia through a participatory approach that involves the workers themselves in the decision-making process and program development. The outcomes are the enhancement insight of the capacity and capability of Indonesian migrant worker unions in Malaysia in advocating for and protecting migrant workers' rights, encourage active participation of migrant workers in union activities and decision-making processes, development empowerment programs based on the real needs of migrant workers, and increasing migrant workers' awareness of their rights and available protection mechanisms.